2003
DOI: 10.1063/1.1534586
|View full text |Cite
|
Sign up to set email alerts
|

Permanent electric dipole moments and hyperfine interaction in ruthenium monocarbide, RuC

Abstract: The [18.1]1∏←X 1∑+ band system of a molecular beam sample of RuC has been recorded field free and in the presence of a static electric field using high resolution laser induced fluorescence spectroscopy. The Stark shifts of the optical features for the 102RuC isotopomer were analyzed to produce permanent electric dipole moments of 3.31(4) and 4.09(14) D for the [18.1]1∏ and X 1∑+ states, respectively. The hyperfine structure associated with spectral features for the 101RuC and 99RuC isotopomers was analyzed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…1-7 A similarly large effort has been made to characterize diatomic transition metal oxides, nitrides, and carbides. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In addition to these pure metallic clusters and diatomic molecules, a handful of more complicated polyatomic organometallic radicals involving open d-subshell transition metals have been investigated using gas phase spectroscopic methods. These include the transition metal methylidynes TiCH, 23 VCH, 24 NbCH, 25 TaCH, 26 and WCH, 27 the dicarbide YC 2 , 28,29 the acetylide YbCCH, 30 and the cyanides CuCN 31 and NiCN.…”
Section: Introductionmentioning
confidence: 99%
“…1-7 A similarly large effort has been made to characterize diatomic transition metal oxides, nitrides, and carbides. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In addition to these pure metallic clusters and diatomic molecules, a handful of more complicated polyatomic organometallic radicals involving open d-subshell transition metals have been investigated using gas phase spectroscopic methods. These include the transition metal methylidynes TiCH, 23 VCH, 24 NbCH, 25 TaCH, 26 and WCH, 27 the dicarbide YC 2 , 28,29 the acetylide YbCCH, 30 and the cyanides CuCN 31 and NiCN.…”
Section: Introductionmentioning
confidence: 99%
“…In many physical chemistry courses, students learn that the molecular Stark effect is used to measure the permanent electric dipole moments l of polar molecules, 7,8 and as a probe of electronic structure and bonding. [9][10][11] An understanding of the molecular Stark effect is key to slowing molecular velocities through Stark deceleration. [12][13][14][15][16] Zeeman slowers [17][18][19] are also an active area of research in atomic physics for slowing velocities and loading particle traps.…”
Section: Introductionmentioning
confidence: 99%
“…1 This is mainly due to the lower ionization potential of carbon that makes the orbitals of carbon nearly degenerate with some of the orbitals of the transition metal. In spite of significant efforts of theoretical [2][3][4][5][6][7][8][9][10][11] and experimental [12][13][14][15][16][17][18][19] chemists, some transition metal carbides, for example, ZrC, are very far from being well characterized. It was not until recently that Rixon et al 18 have reported for the first time that the ground state of ZrC is 3 ⌺ + with three close low-lying 1 ⌺ + states.…”
Section: Introductionmentioning
confidence: 99%